Helicobacter pylori Activates and Expands Lgr5(+) Stem Cells Through Direct Colonization of the Gastric Glands - Sigal, Michael; Rothenberg, Michael E; Logan, Catriona Y; Lee, Josephine Y; Honaker, Ryan W; Cooper, Rachel L; Passarelli, Ben; Camorlinga, Margarita; Bouley, Donna M; Alvarez, Guillermo; Nusse, Roeland; Torres, Javier; et al. (Gastroenterology (New York, N.Y. 1943), 2015)
Helicobacter pylori infection is the main risk factor for gastric cancer. We characterized the interactions of H pylori with gastric epithelial progenitor and stem cells in humans and mice and investigated how these interactions contribute to H pylori-induced pathology. We used quantitative confocal microscopy and 3-dimensional reconstruction of entire gastric glands to determine the localizations of H pylori in stomach tissues from humans and infected mice. Using lineage tracing to mark cells derived from leucine-rich repeat-containing G-protein coupled receptor 5-positive (Lgr5(+)) stem cells (Lgr5-eGFP-IRES-CreERT2/Rosa26-TdTomato mice) and in situ hybridization, we analyzed gastric stem cell responses to infection. Isogenic H pylori mutants were used to determine the role of specific virulence factors in stem cell activation and pathology. H pylori grow as distinct bacterial microcolonies deep in the stomach glands and interact directly with gastric progenitor and stem cells in tissues from mice and humans. These gland-associated bacteria activate stem cells, increasing the number of stem cells, accelerating Lgr5(+) stem cell proliferation, and up-regulating expression of stem cell-related genes. Mutant bacteria with defects in chemotaxis that are able to colonize the stomach surface but not the antral glands in mice do not activate stem cells. In addition, bacteria that are unable to inject the contact-dependent virulence factor CagA into the epithelium colonized stomach glands in mice, but did not activate stem cells or produce hyperplasia to the same extent as wild-type H pylori. H pylori colonize and manipulate the progenitor and stem cell compartments, which alters turnover kinetics and glandular hyperplasia. Bacterial ability to alter the stem cells has important implications for gastrointestinal stem cell biology and H pylori-induced gastric pathology.